Drying Technology Improvement Rengginang to Increase Turn Over Turn Season in Sambigede Village, Malang Regency - Irawan, Dani; Widiyadi; Mindarta, Erwin Komara; Wisnu, Andri; Froidah, Nadia (Talenta Publisher, 2023)
The solution to the problems above that we offer is